“Cutaneous Rabbit” Hops Toward a Light: Unimodal and Cross-Modal Causality on the Skin - Asai, Tomohisa; Kanayama, Noriaki (Frontiers in Psychology, 2012)
Our somatosensory system deals with not only spatial but also temporal imprecision, resulting in characteristic spatiotemporal illusions. Repeated rapid stimulation at the wrist, then near the elbow, can create the illusion of touch at intervening locations along the arm (as if a rabbit is hopping along the arm). This is known as the “cutaneous rabbit effect” (CRE). Previous studies have suggested that the CRE involves not only an intrinsic somatotopic representation but also the representation of an extended body schema that includes causality or animacy perception upon the skin. On the other hand, unlike other multi-modal causality couplings, it is possible that the CRE is not affected by concurrent auditory temporal information. The present study examined the effect of a simple visual flash on the CRE, which has both temporal and spatial information. Here, stronger cross-modal causality or correspondence could be provided. We presented three successive tactile stimuli on the inside of a participant’s left arm. Stimuli were presented on the wrist, elbow, and midway between the two. Results from our five experimental manipulations suggest that a one-shot flash enhances or attenuates the CRE depending on its congruency with cutaneous rabbit saltation. Our results reflect that 1) our brain interprets successive stimuli on the skin as motion in terms of time and space (unimodal causality) and that 2) the concurrent signals from other modalities provide clues for creating unified representations of this external motion (multi-modal causality) as to the extent that “spatiotemporal” synchronicity among modalities is provided.available information from other modalities should also provide a key clue as to the extent that “spatiotemporal” synchronicity among modalities is provided.